An Atelocollagen Coating for Efficient Local Gene Silencing by Using Small Interfering RNA - Olivia Koenig; Dimitrios Nothdurft; Nadja Perle; Bernd Neumann; Andreas Behring; Ilka Degenkolbe; Tobias Walker; Christian Schlensak; Hans Peter Wendel; Andrea Nolte (Elsevier, 2017)
In the last decades, many efforts have been made to counteract adverse effects after stenting atherosclerotic coronary arteries. A breakthrough in better vascular wall regeneration was noted in the new era of drug-eluting stents. A novel personalized approach is the development of gene-eluting stents promising an alteration in gene expression involved in regeneration. We investigated a coating system consisting of the polymer atelocollagen (ATCOL) and a specific small interfering RNA (siRNA) for intercellular adhesion molecule-1 (ICAM-1) found on the surface of defective endothelial cells (ECs). We demonstrated very high cell viability, in which EA.hy926 grew on 0.008% or 0.032% ATCOL layers. Additionally, hemocompatibility assays proved the biocompatibility of this coating. The highest transfection efficiency with EA.hy926 was achieved with 5 μg siRNA immobilized in ATCOL after 2 days. The release of fluorescent-labeled siRNA was about 9 days. Long-term knockdown of ICAM-1 was analyzed by flow cytometry, revealing that the coating with 0.008% ATCOL and 5 μg siICAM-1 provoked gene silencing up to 8 days. 5'-RNA ligase-mediated rapid amplification of cDNA ends PCR (RLM-RACE-PCR) demonstrated the specificity of our established ATCOL gene-silencing coating, meaning that our coating is well suited for further investigations in in vivo studies. Herein, we would like to demonstrate that our ATCOL is well-suited for better artery wall regeneration after stent implantation. Keywords: atherosclerosis, siRNA transfection, local delivery, siICAM-1, gene knockdown, atelocollagen